On the treatment of thermal cracks in lining concrete of water conveyance system of Three Gorges Project permanent ship locks - 王从锋 刘德富 王东东 段亚辉 (Journal of coal science & engineering, China, 2008)
A comprehensive investigation was performed for repairing the different types of cracks appearing on the surface or inside the concrete lining at various depths. The material properties used in grouting and two methods for crack repair were discussed in details, and consequently reliable repair measures were proposed and implemented. It is a better choice to adopt the hole-drilling method for the relatively regular crack. The grouting pressure should not be too high and it is generally between 0.4-0.6 MPa. For the second time grouting, the pressure maybe increased to 0.8 MPa. Other method is the pasting nozzles method which is more suitable for irregular cracks such as cracks with intensive density and crossing cracks. Its grouting pressure is generally between 0.6-1.0 MPa. The in-situ tests in Three Gorges Project demonstrate favorably the feasibility and applicability of the proposed methods for crack repair within the lining concrete.